Functional dairy products:Vol- 2. - Saarela, Maria;Ed (Woodhead Publishing in food science, technology, and nutrition., 2007)
Dairy products have a prominent position in the development of functional foods. As understanding of the health benefits of dairy products increases and consumer awareness of these health benefits grows, demand for new and improved functional dairy products is likely to rise. Functional dairy products: Volume 2 reviews the latest developments in the field and their industrial applications. Part one outlines the health benefits of functional dairy products and their applications in areas such as weight management, child health and gut health. The second part of the book discusses various ingredients used in functional dairy products such as pro- and prebiotics, hypoallergenic hydrolysates and plant sterols and stanols. The final part of the book considers aspects of product development such as biomarkers and experimental models to investigate health benefits, genomics of probiotic microorganisms and functional dairy product regulation and safety. With its distinguished editor and collection of international authors, Functional dairy products: Volume 2, together with its companion volume, provides professionals and researchers within the field with an invaluable reference. Outlines the health benefits of functional dairy products, and their applications in areas such as weight management and gut healthDiscusses ingredients used in functional dairy products such as pro- and prebioticsConsiders various aspects of product development.